Método Montessori para fomentar la autonomía académica de los estudiantes de la unidad educativa “Urdaneta”, provincia de los Ríos, durante el periodo lectivo 2017 - Litardo Inga, Laura Lucrecia (2017)
The present investigation is based on the fact that the students of this institution still learn to say, that they are not yet autonomous, implies that boys and girls are educated in a traditional way, of the observed inside the classroom, the students have not managed to develop the capacity of autonomous learning, and this is due to the teaching-learning process didactista. From this problematization, research has been justified, giving reasons for the importance that this has, and on the other hand, research has been documented, taking as reference what the theories of learning pose, preferably considering the Montessori method, which at , it seems is the most appropriate strategy to promote student autonomy, and similar academic work, which deals with the relationship between the application of the Montessori method and the academic autonomy of students. The research carried out contains important aspects to improve the teaching-learning process, with the implementation of Montessori teaching material for Girls of Second Year of Basic Education; taking advantage of one of the activities of more acceptance of infants such as play-work. Finally, the conclusions and recommendations that we make, according to the implications of this research contrasted with the results of the surveys, the alternative proposal is applied, where as a detail, it describes activities that promote academic autonomy, which is one of the school goals pursued by education in Ecuador.